Composite Open-Web Steel Joists - Tide, Raymond H.R.; Galambos, Theodore V. (Engineering Journal, 1970)
This report presents a description of research on the behavior of composite joists. In this type of structure a concrete slab is connected by shear-connectors to a steeljoist. The research to be described consists of tests on beams. The purpose of the research was to determine the behavior of the shear-connectors.